PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) DI PADU NHT (NUMBERED HEADS TOGETHER) TERHADAP MOTIVASI DAN HASIL BELAJAR KOGNITIF SISWA - Marfani Marfani; Any Fatmawati; Sri Nopita Primawati (Bioscientist : Jurnal Ilmiah Biologi, 2017)
Abstract: Problems in Biology teaching at SMPN 11 Mataram including the teacher’s method applied in the classroom less varied, and effect to the low student motivation of learning. To resolve the problems, cooperative learning model STAD combining with NHT applied in the calssroom.  The purpose of this study is 1) to describe the motivation of students of class VIII SMPN 11 Mataram on the experimental and control classes in the academic year 2016/2017. 2) explain the effect of cooperative learning model STAD combined NHT against cognitive achievement of students in class VIII SMP Negeri 11 Mataram in the academic year 2016/2017. This research is a quasi-experimental with pretest-posttest control group design. Sampling was done by cluster random sampling technique. The population in this study were all students of class VIII SMPN 11 Mataram, the sample used is class VIII B (experimental class) and class VIII E (control group). Data collection techniques using observation sheets, questionnaires motivation and achievement test was performed using multiple choice test. Based on analysis of student motivation in the experimental class and control, the percentage of students' motivation in the experimental class is higher than the control class. Based on the results of hypothesis testing using t-test pooled variance obtained t count higher than t table ie 3.55> 2.00 at the 5% significance level. Therefore, there is the influence of cooperative learning STAD model combined with NHT against cognitive learning outcomes of students of class VIII SMPN 11 Mataram in the academic year 2016/2017.